TINJAUAN KELENGKAPAN PENGISIAN RESUME MEDIS PADA PASIEN RAWAT INAP DI RUMAH SAKIT DR. CIPTO MANGUNKUSUMO - Muhammad Broclin; Yuyun Yunengsih (Bajang Institute, 2021)
Summary of discharge (medical resume) is a summary of the entire period of care and treatment of patients as has been attempted by health workers and related parties. This sheet must be signed by the doctor treating the patient. A discharge summary should be drawn up by the doctor or dentist who treated the patient. The contents of the discharge summary shall at least contain the patient's identity, admission diagnosis and indication of the patient being treated, a summary of the results of the physical and supporting examinations, final diagnosis, treatment and follow-up as well as the name and signature of the doctor or dentist providing health services. The purpose of this study was to determine the completeness of filling out medical resumes for inpatients at Dr. Hospital. Cipto Mangunkusumo. Data collection techniques were carried out by observing filling out medical resumes and conducting interviews with medical record officers. Based on the results of the quantitative analysis recapitulation research from 70 medical records analyzed, the average completeness was 87%, the highest percentage of completeness was in the no tip-ex component of 91%, while the lowest percentage was in the author's authentication component of 81%. To improve the completeness of filling out medical resumes, it is recommended that the medical record unit can socialize the SOP for filling out medical resumes to health workers involved in it and make standards for the completeness of filling out medical records.